Penerapan Pecking Order Theory dan Kaitannya dengan Pemilihan Struktur Modal Perusahaan pada Sektor Manufaktur di Negara Indonesia dan Negara Australia - Iryuvita Januarizka Putri Radjamin; I Made Sudana (Forum Manajemen Indonesia (FMI), 2014)
This study aimed to determine first , the difference between the capital structures in Indonesian manufacturing company with in Australia , and secondly to determine whether manufacturing companies in Indonesia and Australia applying the packing order theory in determining the capital structure . The analysis model used is the comparative analysis between the two groups of independent samples to determine differences in capital structure manufacturing company in Indonesia with a capital structure of manufacturing companies in Australia. Meanwhile, to determine whether manufacturing companies in Indonesia and Australian applying packing order theory, used Shyam - Sunder and Meyers models . The study was conducted on 42 Australian manufacturing companies and 33 manufacturing companies in Indonesia, which is selected by purposive random sampling over the period 2006-20010. The results showed a significant difference between capital structure manufacturing companies in Indonesia and in Australia. Manufacturing companies in Indonesia using long-term debt is relatively higher compared to manufacturing companies in Australia. In addition, it was also found that in determining capital structure manufacturing companies in Indonesia to implement packing order theory, while manufacturing companies in Australia are not . Keywords : Capital Structure, Deficit External Financing, Pecking Order Theory